Fabrication of porous carbons from mesitylene for highly efficient CO2 capture: A rational choice improving the carbon loop - Qi, Shi-Chao; Liu, Yu; Peng, An-Zhong; Xue, Ding-Ming; Liu, Xin; Liu, Xiao-Qin; Sun, Lin-Bing (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
[Display omitted] •Mesitylene is employed as the initial material to synthesize the porous carbons.•Mesitylene molecules linked by methylene groups mimic the lignin behaviors closely.•Porous carbons based on mesitylene well performed on selective carbon capture.•Selective carbon capture in carbonaceous micropores is verified by first-principle. Mesitylene, a representative heavy carbon by-product in the course of C1 chemical downstream processes, is proposed to be employed in this study, as the initial material to synthesize the porous carbons that have played a crucial part in the adsorptive carbon capture process but are generally made from natural carbon resources, instead of fed to the traditional refining process such as hydroprocessing. Based on molecular dynamics calculation, it is proved that once the mesitylene monomers are linked by the flexible methylene groups, the generated polymer can closely mimic the lignin macromolecular behaviors in terms of spatial configuration and atomic thermal motions, which gifts the great potential of the mesitylene-based polymer as applicable a precursor of porous carbon as the biomass-based material. The experimental facts further demonstrate that the porous carbons produced through the routine carbonization of the mesitylene-based polymer can possess desired textural peculiarities, in particular the finely developed micropores that give rise to perfect capacity and selectivity of CO2 capture, of which underlying mechanism is revealed by the first-principle calculation. The porous carbon generated at 700 °C can reach the CO2 capture capacity of 6.16 mmol g−1 at 0 °C and 1 bar, which is much higher than many benchmark materials reported, including some biomass-based porous carbons (2.8 mmol g−1, at 0 °C and 1 bar).